Soil nailing : a practical guide - Cheung, Raymond; Ho, Ken (Boca Raton, FL : CRC Press, 2021)
'This book covers design, construction, quality control, monitoring and maintenance of soil nailing, along with case studies of projects, for practicing engineers and graduate students'--
Includes bibliographical references and index.
Keywords: Soil stabilization; Soil nailing